2011
DOI: 10.1016/j.breast.2011.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics and prognosis of young patients with breast cancer

Abstract: Compared with patients aged between 35 and 50 years, patients aged <35 years have a greater chance of having an endocrine-unresponsive tumor and a significantly poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…The BT and BC survivors in this study are similar to those in other studies in terms of age, gender, disease severity, and treatment [10,[34][35][36][37][38]. The median time since diagnosis was just over 2 years with established impairments and functional disability.…”
Section: Discussionsupporting
confidence: 79%
“…The BT and BC survivors in this study are similar to those in other studies in terms of age, gender, disease severity, and treatment [10,[34][35][36][37][38]. The median time since diagnosis was just over 2 years with established impairments and functional disability.…”
Section: Discussionsupporting
confidence: 79%
“…Breast cancer mortality rates declined about 2% per year over the period 1998 through 2009 (Smith et al, 2014). In addition to government "one-child" policy and the insufficient medical financial appropriation (Lu et al, 2010), Chinese women have their unique physiological features and epidemiological characteristics compared with women in some western developed countries (Han et al, 2011;Li et al, 2011). These lead to a controversy on the application of mammography as a single screening modality for Chinese women in the developing country.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mammography provides an overall view of the breast and facilitates for contrast of the bilateral breasts especially in women with relatively large breasts. However, Chinese patients have their unique physiological features: relatively smaller breasts with denser breast tissue, and an earlier age (before menopause) to contract breast cancer (Fan et al, 2009;Han et al, 2011), as compared to women with breast cancer in western countries. Our data revealed that the mean age of the 306 cases was 51 years, the average breast volume was 528.9 ml, and patients with high-density breast tissue accounted for 82%, which further confirmed Chinese patients' different physiological and epidemiological characteristics from women in western countries.…”
Section: Discussionmentioning
confidence: 99%
“…As compared with cases in some western countries, patients with breast cancer in Asia including China have their unique epidemiological characteristics and physiological features. For example, there are more patients diagnosed at the younger age, and the density of mammary tissue is higher (Fan et al, 2009;Lee et al, 2009;Han et al, 2011;Li et al, 2011). This leads to the controversy on the application of mammography.…”
Section: Introductionmentioning
confidence: 99%